Factors Influencing Undergraduate Students’ Decision to Migrate to Social Network Sites as Part of their Studies - Chalkiadakis, Ioannis; Dania, Aspasia; Adamakis, Manolis; Dimopoulos, Fotios; Chasapis, Iakovos; Christopoulos, Christos (American Journal of Education and Learning, 2022)
Previous research has shown that university students’ decision to use social networks for academic reasons is influenced by several factors. However, until today there is no validated instrument measuring the factors that influence undergraduates to migrate to online networks for educational purposes. The aim of this study was to propose and validate the Push–Pull–Mooring - Physical Education (PPM-PE) questionnaire and examine possible factors that contribute to students’ decisions for social network use. Participants were 302 Physical Education (PE) students from a Greek Faculty of PE and Sport Science. Data analysis with exploratory factor analysis identified a three-factor structure that measured undergraduates’ use of social networks for academic learning purposes. Multivariate analyses of covariance indicated that gender had a significant effect on students’ social networking patterns, while device access did not. Age and hours spent online significantly contributed to the above differences. Findings are discussed in relation to the PPM framework and the idiosyncrasies of online instruction within PE university contexts.